DETERMINANTS OF EARNING PERSISTENCE - Ardela Soehartinah Gunawan; Icih Icih; Trisandi Eka Putri (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2020)
This study aims to determine the effect of firm size, leverage, managerial ownership, listing age and audit committee on earnings persistence. The data used is data on banking companies listed on the Indonesia Stock Exchange (IDX) period 2015-2017. The sample selection uses a purposive sampling method. The samples that fit the criteria were 29 companies during the 2015-2017 observation period, so that the final number of observational data was 87 (3 × 29). Then data were analyzed using the SPSS 22 application.The results of this study indicate that firm size, managerial ownership and listing age do not affect earnings persistence. While leverage and audit committees negatively affect earnings persistence. Variables of company size, leverage, managerial ownership, listing age and audit committee jointly influence the persistence of earnings.